???????? ????? ??????? ?????? ?? ????? ????? ??????? ? ??????? ????? ????? ?????? ?? ??????? ???????? ????????? ???????? ?????? ????????“Cooperative Integrated Reading And Composition” ?????? ????? - Nida Nurun Nabila; Sholehan Sholehan (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
The process of learning Arabic in MTS Negeri 1 Surabaya is still traditional. Especially in reading and writing skills. This causes students difficulty understanding the subject matter. The objectives of this study are: (1) To find out the reading and writing skills of Grade VIII students at MTs Negeri 1 Surabaya. (2) To find out the application of the Cooperative Integrated Reading and Composition